THE STRENGTHENING OF ISLAMIC LAW COMPILATION AS MATERIAL LAW IN INDONESIAN RELIGIOUS COURT - Arip Purkon; Ahmad Hidayat Buang; Mohd Hafiz Jamaludin (al-Afkar, Journal For Islamic Studies, 2022)
Islamic law is an inseparable part of national law in Indonesia. Islamic law has a great opportunity to become national law. One form of Islamic law that has become national law is Islamic Law Compilation. This article examined the existence of Islamic Law Compilation and opportunities for its development, the material content and legal force. This research concluded that: first, although its legal force is still debated, in practice, the Islamic Law Compilation has been used as material law or reference by judges in Indonesian religious courts in deciding cases. Second, the material for Islamic Law Compilation can be deepened and expanded by using a strong ushul fiqh method and can refer to the jurisprudence of judges' decisions, contemporary fatwas from muftis or world religious institutions and scientific studies in the field of Islamic law. Third, to increase the power of law, the Islamic Law Compilation can be fought so that it can become a law.